Experimental investigation on high performance reinforced concrete column with silica fume and fly ash as admixtures - Muthupriya, P.; Subramanian, K.; Vishnuram, B. G. (Journal of Structural Engineering, 2024)
The purpose of this experimental investigation is to study the behavior of short columns produced from High Performance Concrete. In this investigation HPC was manufactured by usual ingredients such as cement, fine aggregate, coarse aggregate, water and mineral admixtures such as silica fume and fly ash at various replacement levels and the Super Plasticizer used was CERAPLAST-300. The water binder ratio (w/b) adopted is 0.30. The concrete used in this investigation was proportioned to target a mean strength of 60 MPa. Specimens such as cubes, cylinders and prism beams were cast and tested for various mixes viz. Seven mixes M1 to M7 are cast with 0%, 5%, 7.5% and 10% replacement of SF and another set of specimens with 0%, 5%, 7.5% and 10% replacement of SF along with 10% constant replacement of fly ash to study the mechanical properties such as compressive strength, split tensile strength and flexural strength at different ages of concrete such as 3, 7, 28, 56 and 90 days. The result shows that the optimum replacement of silica fume is 7.5%. If 10% of fly ash is added the optimum replacement of silica fume is 5%. Totally 7 Columns were cast for mixes M1 to M7. The column specimens were tested in 1000 kN loading frame at 28 days. From this, Load - Mid height deflection (P − Δ) curves were drawn and compared. The same failed columns were rehabilitated with GFRP sheets with one or two layers and again tested in 1000 kN loading frame. The results were then compared with the initial results.